Physical Parameters and Comfort of the School Environment in Assessments of Schoolchildren and Teachers - Ivanova E.V; Nesterova N.V; Vinogradova I.A (Moscow State University of Psychology and Education, 2018)
The problem of interrelation of physical parameters of school space with the state of comfort of students and teachers in conditions of different types of educational environment is considered: "enriched", "standard" and "depleted". The hypothesis was that the assessment of comfort is interrelated with the physical parameters of the environment (temperature, air quality, illumination, acoustics, furniture) and has significant differences in the assessments of schoolchildren and teachers of schools with different types of educational environment. 416 schoolchildren and 73 teachers of three Moscow educational complexes took part in the study. Specially developed questionnaires were used. In the group of schoolchildren, significant differences in assessments of the comfort of the school space and its individual physical parameters were revealed depending on the type of educational environment and significant relationships were established between these indicators. The state of comfort of schoolchildren is determined by the type of educational environment and its physical parameters. For teachers, comfort, which is higher in comparison with the assessments of children, is determined by a favorable psychological climate and benevolent relationships.